The core FOXG1 syndrome phenotype consists of postnatal microcephaly, severe mental retardation, absent language, dyskinesia, and corpus callosum hypogenesis. Issue 6 (25th March 2011) - Kortüm, Fanny; Das, Soma; Flindt, Max; Morris-Rosendahl, Deborah J; Stefanova, Irina; Goldstein, Amy; Horn, Denise; Klopocki, Eva; Kluger, Gerhard; Martin, Peter; Rauch, Anita; Roumer, Agathe; et al.
Abstract : Background: Submicroscopic deletions in 14q12 spanning FOXG1 or intragenic mutations have been reported in patients with a developmental disorder described as a congenital variant of Rett syndrome. This study aimed to further characterise and delineate the phenotype of FOXG1 mutation positive patients. Method: The study mapped the breakpoints of a 2;14 translocation by fluorescence in situ hybridisation and analysed three chromosome rearrangements in 14q12 by cytogenetic analysis and/or array comparative genomic hybridisation. The FOXG1 gene was sequenced in 210 patients, including 129 patients with unexplained developmental disorders and 81 MECP2 mutation negative individuals. Results: One known mutation, seen in two patients, and nine novel mutations of FOXG1 including two deletions, two chromosome rearrangements disrupting or displacing putative cis -regulatory elements from FOXG1, and seven sequence changes, are reported. Analysis of 11 patients in this study, and a further 15 patients reported in the literature, demonstrates a complex constellation of features including mild postnatal growth deficiency, severe postnatal microcephaly, severe mental retardation with absent language development, deficient social reciprocity resembling autism, combined stereotypies and frank dyskinesias, epilepsy, poor sleep patterns, irritability in infancy, unexplained episodes of crying, recurrent aspiration, and gastro-oesophageal reflux. Brain imaging studies reveal simplified gyral pattern and reduced white matter volume in the frontal lobes, corpus callosum hypogenesis, and variable mild frontal pachgyria. Conclusions: These findings have significantly expanded the number of FOXG1 mutations and identified two affecting possible cis -regulatory elements. While the phenotype of the patients overlaps both classic and congenital Rett syndrome, extensive clinical evaluation demonstrates a distinctive and clinically recognisable phenotype which the authors suggest designating as the FOXG1 syndrome.